2015
DOI: 10.3171/2014.10.jns141101
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of high-frequency hearing loss after microvascular decompression for trigeminal neuralgia, glossopharyngeal neuralgia, or geniculate neuralgia

Abstract: S enSorineural hearing loss after microvascular decompression (MVD) has a reported incidence of 1%-23.8% when performed for trigeminal neuralgia (TGN), 1.5%-4.2% for glossopharyngeal neuralgia (GPN), and 22% for geniculate neuralgia (GN). 21,24,25,27 Because of the proximity of the cranial nerve VIII to cranial nerves decompressed during the procedure, the auditory nerve in many patients is often stretched or damaged, resulting in hearing impairment. Although sensorineural hearing loss after MVD is frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Should both techniques fail, we recommend exposure of the internal acoustic canal and retrograde tracing of the NI; however, this should be reserved as a last resort, given the potential for increased risk of facial nerve injury, deafness, vestibulopathy, and CSF leak due to temporal bone drilling. 1,7,13,15,16 The results of our study are subject to several significant limitations, including small cohort sizes in both the primary and repeat surgery groups, short median follow-up of 11 months, and the inherent risks of bias and confounding that are associated with any retrospective analysis. With respect to the systematic review, the included studies were scattered over a broad range of years and techniques, outcomes were reported inconsistently and heterogeneously, and the small sample sizes and inconsistent data prohibited formal statistical analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Should both techniques fail, we recommend exposure of the internal acoustic canal and retrograde tracing of the NI; however, this should be reserved as a last resort, given the potential for increased risk of facial nerve injury, deafness, vestibulopathy, and CSF leak due to temporal bone drilling. 1,7,13,15,16 The results of our study are subject to several significant limitations, including small cohort sizes in both the primary and repeat surgery groups, short median follow-up of 11 months, and the inherent risks of bias and confounding that are associated with any retrospective analysis. With respect to the systematic review, the included studies were scattered over a broad range of years and techniques, outcomes were reported inconsistently and heterogeneously, and the small sample sizes and inconsistent data prohibited formal statistical analysis.…”
Section: Discussionmentioning
confidence: 96%
“…[ 2 ] As IONMs, BAEP and facial MEP plays important roles in avoiding hearing loss and facial paresis after MVD, not only for hemifacial spasm (HFS), but also for GN. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Surgical corridors used in each operation were determined by both the operative notes and videos made during intraoperative microscopic recording. We eventually used the lateral corridor in 219 (52.1%) cases, the medial corridor in 175 (41.7%) cases, and the intermediate corridor in 26 ing of the vein anchor point occurred in 4 cases via the lateral corridor after gelatin compression hemostasis was achieved, and the surgical approach was changed immediately to the medial or intermediate corridor.…”
Section: Intraoperative Assessmentmentioning
confidence: 99%
“…vein itself must be cut off, which undoubtedly increases the possibility of vein injury, 5,18 cerebellar edema or hematoma, 8,17 hearing impairment, 26 facial paralysis, 2 or a life-threatening event. 1 Fujimaki and Kirino 9 and Zhu and coworkers 28 described the transhorizontal, or cerebellar-fissure, approach in MVD surgery for decreasing the risk of petrosal vein and seventh cranial nerve injury.…”
mentioning
confidence: 99%